African Students Watching CCTV-Africa: A Structural Reception Analysis of Oppositional Decoding. (21st June 2018) - Xiang, Yu
The 'going global' strategy of China's outbound media has been running for about ten years. The main beneficiary, China Central Television (CCTV) has enhanced its global presence through institutional expansion. The growing influence of CCTV-Africa, as one of CCTV's major media hubs overseas, is arousing wide discussions in regard to its agenda and journalistic practice as one part of the state media of China. How the role of CCTV-Africa is interacting with the grander structure of Africa-China multilateral relations has been the main focus of scholars' discursive enquiries. Despite the increasing focus of scholars on the institutional behaviours or media content of CCTV-Africa, the subject of audience reception is under-studied. This research aims to contribute to the field by analysing media reception of a specific group of African students in China from the perspective of structural theories of international communication. Based on the findings of in-depth individual interviews with 38 interviewees (with a particular focus on the oppositional decoding of four interviewees) and frame analysis of CCTV-Africa news, this research reached a theoretical conclusion, concerning the articulation of the alternative reception of transnational audiences. Although the decoding positions of such an audience can be polynary the objective environment (intranational political and economic agenda as structural dominance) limits the projection of alternative opinions into constructive articulation in real life.